2018
DOI: 10.1186/s40644-018-0135-y
|View full text |Cite
|
Sign up to set email alerts
|

18F–FDG-PET/CT and diffusion-weighted MRI for monitoring a BRAF and CDK 4/6 inhibitor combination therapy in a murine model of human melanoma

Abstract: BackgroundThe purpose of the study was to investigate a novel BRAF and CDK 4/6 inhibitor combination therapy in a murine model of BRAF-V600-mutant human melanoma monitored by 18F–FDG-PET/CT and diffusion-weighted MRI (DW-MRI).MethodsHuman BRAF-V600-mutant melanoma (A375) xenograft-bearing balb/c nude mice (n = 21) were imaged by 18F–FDG-PET/CT and DW-MRI before (day 0) and after (day 7) a 1-week BRAF and CDK 4/6 inhibitor combination therapy (n = 12; dabrafenib, 20 mg/kg/d; ribociclib, 100 mg/kg/d) or placebo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The therapeutic effectiveness of CAP treatment in MM was substantiated by the reduction in cellularity in week three, i.e., a significant increase in ADC values, while ADC values only slightly increased in CAP-treated SCC mice. This is in line with data from Eschbach et al who also showed that tumour therapy with BRAF and CDK 4/6 inhibitors increased the ADC values of MM in mice, compared to non-treated tumours [39]. Furthermore, reduced cellularity in tumours, i.e., an increase in ADC values, is an established parameter for the assessment of a therapeutic response in humans [40].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The therapeutic effectiveness of CAP treatment in MM was substantiated by the reduction in cellularity in week three, i.e., a significant increase in ADC values, while ADC values only slightly increased in CAP-treated SCC mice. This is in line with data from Eschbach et al who also showed that tumour therapy with BRAF and CDK 4/6 inhibitors increased the ADC values of MM in mice, compared to non-treated tumours [39]. Furthermore, reduced cellularity in tumours, i.e., an increase in ADC values, is an established parameter for the assessment of a therapeutic response in humans [40].…”
Section: Discussionsupporting
confidence: 87%
“…The reduced MTV could be an indication of the therapeutic effect of the CAP treatment, similar to the increase in ADC values after the CAP treatment. It has already been shown in an in vivo study with MM that the treatment response was indicated by an increased ADC value and also a reduced uptake of 18 [F]FDG [39]. It cannot be excluded that partial volume effects, or the limited spatial resolution of the PET could have obscured a decrease in MTV after CAP treatment, although we only included the 40% of the hottest voxels in the tumour VOI to reduce partial volume effects.…”
Section: Discussionmentioning
confidence: 99%
“…Palbociclib also exerted a potent anti-tumor activity in vivo, inducing a robust growth suppression in xenografts derived from different tumors types, including breast cancer [ 28 , 29 ]. Ribociclib has demonstrated in vivo anti-tumor activity in different tumor xenograft models including breast, melanoma, neuroblastoma, malignant rhabdoid, lung, pancreas, and hematological malignancies [ 35 , 36 , 37 , 38 ]. In addition, ribociclib has shown anti-tumor activity when combined with targeted agents which inhibit signaling pathways known to regulate D-cyclin levels, including inhibitors of the RAF, mitogen-activated protein kinase kinase (MEK), phosphoinositide 3-kinase (PIK3), and mammalian target of rapamycin (mTOR) pathways [ 35 , 39 , 40 ].…”
Section: Pharmacological Activity Of Cdk4/6 Inhibitorsmentioning
confidence: 99%
“…Ribociclib has demonstrated in vivo anti-tumor activity in different tumor xenograft models including breast, melanoma, neuroblastoma, malignant rhabdoid, lung, pancreas, and hematological malignancies [ 35 , 36 , 37 , 38 ]. In addition, ribociclib has shown anti-tumor activity when combined with targeted agents which inhibit signaling pathways known to regulate D-cyclin levels, including inhibitors of the RAF, mitogen-activated protein kinase kinase (MEK), phosphoinositide 3-kinase (PIK3), and mammalian target of rapamycin (mTOR) pathways [ 35 , 39 , 40 ]. In ER-positive (ER+) breast cancer xenograft models, combinations of ribociclib with endocrine therapy such as letrozole, fulvestrant, and tamoxifen demonstrate a statistically significant, strong, and sustained antitumor activity compared to endocrine therapy or ribociclib alone [ 41 ].…”
Section: Pharmacological Activity Of Cdk4/6 Inhibitorsmentioning
confidence: 99%
“…To investigate the metabolic activity of NPC xenograft models, we rst tested the repeatability of the microPET/MR system. The glucose uptake of liver in mice was reported stable upon fasting condition in several studies [27,28] and SUVmean_liver has been used as the background to normalize radiotracer accumulation [29]. Thus, in our study SUVmean_liver was used to examine the repeatability of the microPET/MR imaging system.…”
Section: Repeatability Of [ 18 F]fdg Micropet/mr Imaging System For Suv Measurementmentioning
confidence: 96%